2006
DOI: 10.1111/j.1365-246x.2006.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Joint geodynamical and seismic modelling of the Eifel plume

Abstract: S U M M A R YTeleseismic P-wave tomography has revealed a columnar low-velocity anomaly in the upper mantle below the volcanic Eifel region in western Germany extending to at least 400 km depth.Here we explore whether a geodynamically consistent model of a mantle plume can explain the observed traveltime residuals. We use a 3-D mantle convection code with temperature and pressure-dependent viscosity to generate a suite of model plumes that rise from the transition zone and spread below a stationary or drifting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(51 reference statements)
1
6
0
1
Order By: Relevance
“…These values defi ne a buoyancy fl ux estimate of 0.03-0.1 Mg/s for a plume excess temperature of 70-200 °C, consistent with estimates from other methods (Waite, 2004). This buoyancy fl ux is much smaller than the 8 Mg/s buoyancy fl ux estimated for the Hawaiian plume (Sleep, 1990), but close to the 0.5-1.0 Mg/s fl ux proposed for the Eifel plume (Wüllner et al, 2006). The excess temperature found by our analysis, combined with the tomographic and mantle velocity discontinuity results (Fee and Dueker, 2004;Waite et al, 2006;Yuan and Dueker, 2005), strongly suggests that the ultimate cause of the Yellowstone hotspot track is a thermal mantle plume.…”
Section: Discussionsupporting
confidence: 54%
“…These values defi ne a buoyancy fl ux estimate of 0.03-0.1 Mg/s for a plume excess temperature of 70-200 °C, consistent with estimates from other methods (Waite, 2004). This buoyancy fl ux is much smaller than the 8 Mg/s buoyancy fl ux estimated for the Hawaiian plume (Sleep, 1990), but close to the 0.5-1.0 Mg/s fl ux proposed for the Eifel plume (Wüllner et al, 2006). The excess temperature found by our analysis, combined with the tomographic and mantle velocity discontinuity results (Fee and Dueker, 2004;Waite et al, 2006;Yuan and Dueker, 2005), strongly suggests that the ultimate cause of the Yellowstone hotspot track is a thermal mantle plume.…”
Section: Discussionsupporting
confidence: 54%
“…However, an opposite HS would not, by itself, predict a plume that is more consistent with flow predictions. Although APM is very different from previous estimates (and, if wrong, could be the cause of the anomalous plume ), independent evidence of shallow, APM‐controlled, tilting of the Eifel plume toward the NNE [ Wüllner et al , 2006] suggests that GSRM‐APM‐1 properly describes APM in Europe (albeit some mm/a slower than Wüllner et al [2006] found).…”
Section: Implications For Mantle Flowmentioning
confidence: 81%
“…The v s anomaly is absent between 170 and 240 km depth and has a large E‐W extension below. The anomalous low v P beneath the West Eifel can be explained by 200°C excess temperatures in the upper mantle up to 1200–1300°C, a few percent of partial melts (Ritter, 2007), and a buoyancy flux of 500–1,000 kg/s (Wüllner et al, 2006). The measured heat flux in the WEVF of 70–80 mW/m 2 is lower than expected from a deep mantle plume assuming steady‐state conductive heat transfer, indicating that the thermal perturbation beneath the Eifel is possibly small (Seck & Wedepohl, 1983).…”
Section: Magmatic Systems Beneath the Rhm: State Of Knowledgementioning
confidence: 99%
“…The Quaternary WEVF and EEVF occur above a 100 km broad seismic S wave anomaly in the upper mantle and a broader region of Moho upwelling as documented by receiver functions (Figure 1). Therefore, a plume‐like upwelling of asthenospheric and lithospheric mantle rocks has been suggested (Ritter et al, 2001), which may possibly have even deeper roots in a lower mantle plume with a stem radius of 60 km and a center about 50 km to the S of the WEVF and 80 km S‐SW of the EEVF (Ritter, 2007; Wüllner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%